Schistura larketensis, a new cavernicolous fish (Teleostei: Nemacheilidae) from Meghalaya, Northeast India - Choudhury, Hrishikesh; Mukhim, D. Khlur B.; Basumatary, Sudem; Warbah, Deisakee P.; Sarma, Dandadhar (Zootaxa, 2017)
Schistura larketensis, a new species of cavernicolous loach, is described from Khung, a limestone cave in Meghalaya, India. The species differs from Schistura papulifera, its only troglomorphic congener from northeast India, in having a smooth ventral surface of the head, the presence of a small cylindrical axillary pelvic lobe, and the presence of three pores in the supratemporal canal of the cephalic lateral-line system. Apart from these differences, the species can be immediately distinguished from all other species of Schistura from the Brahmaputra River and neighboring basins by the complete absence (or only vestigial presence) of eyes.